PENERAPAN PENDEKATAN PROBLEM SOLVING PADA MATERI SIFAT KOLIGATIF LARUTAN DI MAN MODEL BANDA ACEH TAHUN AJARAN 2012/2013 - Nuraini Nuraini (Chimica Didactica Acta)
The research about Application Problem Solving Approach to content colligative properties of solution in MAN Model Banda Aceh aims to determine student learning yield, student activities, and student responses after given problem solving approach used in learning. The subjects of the research were 32 students of class XII-IA2 MAN Model Banda Aceh in academic year 2012/2013, with heterogenous acchivement. Data collection was conducted through written tests and observations. Based on objective tests given after the study ended, student learning yield was obtained very good with the level of completeness of 96.67%. Activity of student suggests that a good percentage of the activity (79.82%). The response of students to the problem solving approach learning shows that students gave a positive response is very good (91.52%). Thus, it is conclused that applying of problem solving approach to the material colligative properties of solution can increase student learning yield, activities, and student motivation.